A well-defined unimolecular channel facilitates chloride transport. Issue 10 (17th January 2018) - Chen, Sujun; Zhao, Yongliang; Bao, Chunyan; Zhou, Yaowu; Wang, Chenxi; Lin, Qiuning; Zhu, Linyong
Abstract : A well-defined unimolecular channel was optimized for Cl − transport and its fluorescence feature endowed visualization for channel insertion in a membrane. Abstract : A unimolecular ion channel was optimized by functionalization with a new type of rigid-rod oligomer. The macrocycle pendant endows chloride selectivity and the fluorescence feature and suitable length of the rod facilitates the visual insertion of channels into the lipid bilayer, resulting in efficient ion transport with an EC50 value of 0.36 μM.